Menjadi Jembatan Kasih di Dunia Maya: Analisis Fenomena Solidaritas Lintas Iman dalam Konteks Ramadan di Indonesia - Skolastika Dinda Ayu Maharani; Monica Innanda Chiaralazzo; Intan Sakti Pius X (Berkat : Jurnal Pendidikan Agama dan Katolik, 2026)
This article examines the phenomenon of interfaith solidarity rapidly flourishing in Indonesia’s digital sphere during Ramadan, specifically through the viral "war takjil" trend involving active participation from non-Muslim communities. With national social media users reaching 180 million, digital platforms have transformed into crucial interaction spaces facilitating fluid and participatory interfaith communication. This research employs a qualitative approach using literature review, phenomenological analysis, and theological reflection within the Catholic tradition to understand the meaning behind this social behavior. Main findings indicate that this phenomenon is a concrete manifestation of bottom-up pluralism, emerging organically from daily social interactions. Based on the Contact Hypothesis, these digital interactions successfully reduce prejudice by achieving common goals and maintaining equal status in public spaces. Theologically, the phenomenon reflects the spirit of universal brotherhood and solidarity emphasized in the documents Fratelli Tutti and Nostra Aetate. The article concludes that healthy pluralism is the capacity to maintain one's own faith identity while actively building bridges of love with those of different beliefs. The implications emphasize the importance of media literacy for faith educators and catechists to guide the community in responding to digital social dynamics constructively without compromising theological truths. This study serves as a reference for developing inclusive, love-based interfaith communication strategies within Indonesia’s diverse digital society.